1983
DOI: 10.1007/bf00427822
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of intravenously given alcohol on saccadic eye movements and subjective evaluations of intoxication

Abstract: Effects of intravenously given alcohol on eye movements were analysed in ten voluntary subjects. Each subject served as his/her own control. Good correlations were found between the changes in saccade variables and subjective evaluations of alertness, eye movement control and intoxication. Interindividually, the subjective evaluation of drunkenness correlates with the alcohol effect on saccade variables better than do the other subjective variables or blood or breath alcohol concentrations. A steady decrease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 15 publications
5
21
1
1
Order By: Relevance
“…In close agreement with a number of earlier reports [15][16][17][18] , our study confirmed that visually evoked reflexive saccadic eye movements were markedly altered under the influence of alcohol. Latencies were slightly increased during the rise of the BAC level and shorter during its decline, whereas the main sequence parameters (V max , τ) were clearly reduced at any time after exposure to alcohol.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In close agreement with a number of earlier reports [15][16][17][18] , our study confirmed that visually evoked reflexive saccadic eye movements were markedly altered under the influence of alcohol. Latencies were slightly increased during the rise of the BAC level and shorter during its decline, whereas the main sequence parameters (V max , τ) were clearly reduced at any time after exposure to alcohol.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have previously established that saccade latencies are prolonged and peak eye velocities are reduced under the influence of moderate-to-high levels of blood alcohol values [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…The vehicle injections did not by themselves produce significant reductions in SEV compared to baseline in either group or cycle phase, but it is quite conceivable that a repeated measures ANOVA would have detected a significant SEV reduction over time. Ethanol itself has positive modulatory effects at GABA A receptors [44], and is known to reduce the SEV [45]. It is therefore likely that the small amount of ethanol present in the vehicle solution would have been able to induce changes in SEV response over time in sensitive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of drugs have been shown to affect all these measures of saccadic eye movement. Thus alcohol has been shown to reduce saccadic velocity, though not latency (Wilkinson, 1976;Wilkinson et al, 1979;Jantti et al, 1983), and the additive effects of marijuana and alcohol on the reduction of both saccadic maximum velocity and reaction time have been demonstrated by Baloh and coworkers (1979). Diazepam and other benzodiazepines have been shown to produce dose dependent increases in saccadic duration and decreases in saccadic velocity (Jurgens et al, 1981;Rothenberg & Selkoe, 1981a;Bittencourt et al, 1981;Salonen et al, 1986).…”
Section: Discussionmentioning
confidence: 96%